NEW SPECIES OF CLIMBING AND SCRAMBLING BAMBOO FROM SULAWESI, INDONESIA - Dita Ervianti; Elizabeth Anita Widjaja; Agung Sedayu (Reinwardtia, 2019)
ERVIANTI, D., WIDJAJA, E. A. & SEDAYU, A. 2019. New species of climbing and scrambling bamboo from Sulawesi, Indonesia. Reinwardtia 18(2): 115−132 — Ten new species of Sulawesi bamboos are discovered, belonging to the climbing genus Dinochloa Büse and the scrambling Fimbribambusa Widjaja. These are Dinochloa bungintimbensis Widjaja & Ervianti, D. glabra Widjaja & Ervianti, D. karaboensis Widjaja & Ervianti, D. khoonmengii Widjaja & Ervianti, D. kolakaensis Widjaja & Ervianti, D. mekonggensis Widjaja & Ervianti, D. multibrachiata Widjaja & Ervianti, D. sessilifolia Widjaja & Ervianti, D. wartabonei Widjaja & Ervianti, and Fimbribambusa soejatmiae Widjaja & Ervianti. Identification keys, descriptions and illustrations of these species are presented.